2008
DOI: 10.1143/jjap.47.7436
|View full text |Cite
|
Sign up to set email alerts
|

Role of Negative Electric Field Biasing on Growth of Vertically Aligned Carbon Nanotubes Using Chemical Vapor Deposition

Abstract: A new method of manufacturing Mollenstedt electron spectrometer entrance slits is described. The new slits have radically improved performance and service life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…First, nickel (Ni) particles were deposited as a catalyst on the apex of the W whisker by RF magnetron plasma processing (100 W net power) for 40 s. The multiwalled carbon nanotubes (MWCNTs) were grown by chemical vapour deposition (CVD) on the W whisker substrate [14,15]. After 10 min of pretreatment by ammonia (NH 3 ) gas, the CNTs' growth process was performed for 5-15 min under the following conditions: the gas flow rates of NH 3 and C 2 H 2 were 150 sccm and 50 sccm, respectively, the pressure was fixed at 30 Torr and the stage heating temperature was 900 • C. A key point in obtaining vertically aligned CNTs is applying a dc voltage during the growth process [16]. In our experiment −100 V dc was applied between the whisker and a Ti mesh situated at a distance of approximately 2 mm.…”
Section: Methodsmentioning
confidence: 99%
“…First, nickel (Ni) particles were deposited as a catalyst on the apex of the W whisker by RF magnetron plasma processing (100 W net power) for 40 s. The multiwalled carbon nanotubes (MWCNTs) were grown by chemical vapour deposition (CVD) on the W whisker substrate [14,15]. After 10 min of pretreatment by ammonia (NH 3 ) gas, the CNTs' growth process was performed for 5-15 min under the following conditions: the gas flow rates of NH 3 and C 2 H 2 were 150 sccm and 50 sccm, respectively, the pressure was fixed at 30 Torr and the stage heating temperature was 900 • C. A key point in obtaining vertically aligned CNTs is applying a dc voltage during the growth process [16]. In our experiment −100 V dc was applied between the whisker and a Ti mesh situated at a distance of approximately 2 mm.…”
Section: Methodsmentioning
confidence: 99%
“…The global electric fields lie somewhere between 0.1 and 0.5 V/µm. The combined findings of [19,20,47,48] indicate that an electric field in the range of 0.1–2.0 V/µm is necessary to achieve alignment, values that are consistent with these extremities. Note, also, that Jang et al [21] reported negligible improvements in the alignment “quality” for fields >2.0 V/µm, whilst Ural et al [19] found an optimal field of 0.1 V/µm.…”
Section: Resultsmentioning
confidence: 70%
“…Here, the Pd nanoparticles act as catalyst for carbon nanotube growth. 6,7 In Fig. 3 the total experimental procedure is schematically shown.…”
Section: Methodsmentioning
confidence: 99%
“…In this article, we report the use of this technique for the growth of carbon nanotubes from palladium catalyst particles 6 on an electrically insulating surface. 7 We shall first discuss the basic principle of defining charge patterns in an insulator with a finely focused electron beam, the basic working of the glowing wire generator and the deposition of charged nanoparticles, and finally the results of carbon nanotube growth on predefined positions.…”
Section: Introductionmentioning
confidence: 99%